EVALUASI PELATIHAN MEMBACA GAMBAR TEKNIK UNTUK TIM SALES DAN PRODUKSI PADA PT. ISTW JAKARTA - Casban ST MT; Umi Marfuah; Ariya Purnamasari Dewi; Didi Sunardi (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
Training on reading technical drawings carried out in community service activities for the UMJ industrial engineering lecturer team can broaden the horizons, knowledge and abilities of partners in reading technical drawings. This study aims to measure the success of training activities based on the CIPP (Context, Input, Process, Product) evaluation model. This evaluation research design uses the stages of evaluation of the CIPP model through a qualitative descriptive approach. Partners in community service activities are the sales and production team at PT. ISTW Jakarta. Data collection techniques used questionnaires, interviews, documentation and literature review. The steps of research activities are carried out by determining the focus of the evaluation, designing the evaluation, collecting information, analyzing information and reporting the results of the evaluation. The results of data analysis can be concluded based on the context evaluation aspect, it can be seen that the training materials can provide benefits and the training topics attract partners' interest. The input aspect of the evaluation can be seen that the speaker can master the material presented and the implementation of online training is appropriate during the covid-19 pandemic. Aspects of the evaluation process can be seen that the training material can be understood well, the method of delivering the material has been made systematically and the delivery of the material has been done well. Aspects of product evaluation can be seen that training materials are needed in carrying out tasks, improving skills at work and partners require further deepening of training